2019
DOI: 10.1111/dth.13178
|View full text |Cite
|
Sign up to set email alerts
|

Skin graft storage in platelet rich plasma (PRP)

Abstract: Storage of skin grafts for later use is one of the standard applications in surgery. It is the most preferred method to maintain at +4 C in refrigeration after wrapping the surplus grafts into sterile gauze pad moistened with saline. Although there are many studies on the storage of skin grafts, less is known about storing skin grafts with PRP.Twenty-five pieces of 1 × 1 cm 2 partial thickness skin graft were harvested from 12 patients during the reduction mammoplasty operation. Twenty-four grafts were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The aesthetic unit of the face must be considered during excision, which can often be performed using a hydrosurgery system such as Versajet (Smith & Nephew, Hull, UK) for shallow partial thickness burns (see image below). When excising burns on the dorsum of the hand, special care must be taken to avoid injury to the extensor tendons and peritenon in order to provide a vascularized bed for the corrupted to recover and maintain maximal postoperative hand function (Fukuoka et al, 2021;Gokkaya et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The aesthetic unit of the face must be considered during excision, which can often be performed using a hydrosurgery system such as Versajet (Smith & Nephew, Hull, UK) for shallow partial thickness burns (see image below). When excising burns on the dorsum of the hand, special care must be taken to avoid injury to the extensor tendons and peritenon in order to provide a vascularized bed for the corrupted to recover and maintain maximal postoperative hand function (Fukuoka et al, 2021;Gokkaya et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The practical impact of the available data is the current recommendation that skin grafts be stored in saline for a maximum of 10 days before use. Grafts stored in this way for 10 days do not show changes affecting the overall viability of the graft [3,4]. ment of extensive burns.…”
Section: Discussionmentioning
confidence: 97%
“…This protocol may explain why their samples in saline were affected by maceration, since PRP has a higher viscosity [1]. In another study, Gokkaya et al reported that the samples stored in PRP had better final appearance, when examined macroscopically, although the final storage time did not significantly differ between samples stored in PRP versus saline [3].…”
Section: Keskin Et Al Demonstrated That Prp Influencedmentioning
confidence: 99%
See 2 more Smart Citations